Regression analysis in the process of studying the correlation between climate factors of the Chisinau weather station - Puțuntică, Anatolie; Puțuntică, Vitalie (Acta et Commentationes Exact and Natural Sciences, 2023)
The study presents linear and nonlinear mathematical models that analyze the regression in the process of correlation between climatic factors. The elaborated research is carried out for the period 1960-2019, analyzing the experimental data of the average annual temperature and the amount of annual precipitation. Various forms of regressions (linear, parabolic, cubic, etc.) and predictions for the correlation between the year and the average annual temperature, the year and the amount of annual precipitation, the average annual temperature and the amount of annual precipitation were obtained.